Eight-Year Follow-Up of an Initial Case with NF-κB Decoy Oligodeoxynucleotide Transfection After Coronary Stent Implantation - Suzuki, Jun-ichi; Tezuka, Daisuke; Morishita, Ryuichi; Isobe, Mitsuaki (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2012)
Background: Nuclear factor–kappa B (NF-κB) plays a pivotal role in vascular remodeling after percutaneous coronary intervention (PCI) with a stent implantation. Methods and Results: This is the first clinical report to demonstrate the effect of NF-κB decoy oligodeoxynucleotide (ODN) on the prevention of restenosis after an eight-year observation period. We revealed that decoy ODN treatment suppressed neointimal formation in comparison to that without ODN transfected stent lesion in the same artery. Conclusion: We showed the long-term usefulness of NF-κB decoy ODN transfer after PCI.
Keywords: stents